Safety and Efficacy of Cangrelor in Acute Stroke Treated with Mechanical Thrombectomy: Endovascular Treatment of Ischemic Stroke Registry and Meta-analysis - Marnat, G.; Finistis, S.; Delvoye, F.; Sibon, I.; Desilles, J.-P.; Mazighi, M.; Gariel, F.; Consoli, A.; Rosso, C.; Clarençon, F.; Elhorany, M.; Denier, C.; et al. (American journal of neuroradiology : AJNR, 2022)
Rescue therapies are increasingly used in the setting of endovascular therapy for large-vessel occlusion strokes. Among these, cangrelor, a new P2Y12 inhibitor, offers promising pharmacologic properties to join the reperfusion strategies in acute stroke. We assessed the safety and efficacy profiles of cangrelor combined with endovascular therapy in patients with large-vessel-occlusion stroke. We performed a retrospective patient data analysis in the ongoing prospective multicenter observational Endovascular Treatment in Ischemic Stroke Registry in France from July 2018 to December 2020 and conducted a systematic review and meta-analysis using several data bases. Indications for cangrelor administration were rescue strategy in case of refractory intracranial occlusion with or without intracranial rescue stent placement, and cervical carotid artery stent placement in case of cervical occlusion (tandem occlusion or isolated cervical carotid occlusion). In the clinical registry, 44 patients were included (median initial NIHSS score, 12; prior intravenous thrombolysis, 29.5%). Intracranial stent placement was performed in 54.5% ( = 24/44), and cervical stent placement, in 27.3% ( = 12/44). Adjunctive aspirin and heparin were administered in 75% ( = 33/44) and 40.9% ( = 18/44), respectively. Rates of symptomatic intracerebral hemorrhage, parenchymal hematoma, and 90-day mortality were 9.5% ( = 4/42), 9.5% ( = 4/42), and 24.4% ( = 10/41). Favorable outcome (90-day mRS, 0-2) was reached in 51.2% ( = 21/41), and successful reperfusion, in 90.9% ( = 40/44). The literature search identified 6 studies involving a total of 171 subjects. In the meta-analysis, including our series data, symptomatic intracerebral hemorrhage occurred in 8.6% of patients (95% CI, 5.0%-14.3%) and favorable outcome was reached in 47.6% of patients (95% CI, 27.4%-68.7%). The 90-day mortality rate was 22.6% (95% CI, 13.6%-35.2%). Day 1 artery patency was observed in 89.7% (95% CI, 81.4%-94.6%). Cangrelor offers promising safety and efficacy profiles, especially considering the complex endovascular reperfusion procedures in which it is usually applied. Further large prospective data are required to confirm these findings.